PENGARUH PENGGUNAAN SISTEM PEMBAYARAN DIGITAL OLEH UMKM TERHADAP KEPATUHAN WAJIB PAJAK - Hadija, Siti; Muchran, Muchriana; Rayyani, Wa Ode (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid growth of digital technology has transformed financial transaction patterns, including in the taxation sector. This study aims to examine and analyze the effect of digital payment system use by Micro, Small, and Medium Enterprises (MSMEs) on taxpayer compliance in Makassar City. The independent variable is the use of digital payment systems, while the dependent variable is taxpayer compliance. This research employed a quantitative approach using primary data collected through questionnaires distributed to 100 MSME respondents registered at KPP Pratama North Makassar, selected through purposive sampling. Data were processed using simple linear regression analysis with SPSS version 27. The research instrument validity was confirmed through Pearson correlation tests, with all items showing r-count values exceeding r-table (0.196) at a significance level below 0.05. Reliability testing using Cronbach's Alpha produced values of 0.993 for the digital payment variable and 0.992 for the taxpayer compliance variable, both exceeding the 0.60 threshold. Classical assumption tests including normality, multicollinearity, and heteroscedasticity tests were all satisfied. The results show a regression coefficient of 0.737 with t-count of 65.501 greater than t-table (1.984) and significance value of 0.001 below 0.05. The coefficient of determination (R²) reached 0.978, indicating that digital payment systems explain 97.8% of the variation in taxpayer compliance. These findings confirm that digital payment system adoption by MSMEs has a positive and significant effect on taxpayer compliance, as digital technology facilitates more transparent, accurate, and efficient transaction recording, thereby encouraging taxpayer awareness and compliance in fulfilling tax obligations.